The Influence of Job Satisfaction and Self-Efficacy on Employee Performance through Organizational Commitment as An Intervening Variable - Ayuwangi, Bunga; Hadi, Hafid Kholidi; Wardoyo, Dewie Tri Wijayati; Budiono, Budiono (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to determine and analyze the influence of job satisfaction and self-efficacy variables on employee performance through organizational commitment as an intervening variable at PT. Telkom Access Kediri Sampling using a proportionate stratified random sampling technique amounted to 146 respondents. Data was collected by distributing questionnaires whose validity and reliability were tested to ensure data accuracy and consistency. Data analysis was carried out using SmartPLS software version 3.9.9. This research tests the hypothesis using the Structural Equation Model (SEM) with the Partial Least Square (PLS) analysis method. The measurement scale in this study uses a Likert scale. The results of this research explain that job satisfaction has a positive and significant effect on employee performance. Self-efficacy has a positive and significant effect on employee performance. Organizational commitment has a positive and significant effect on employee performance. Job satisfaction has a positive and insignificant effect on organizational commitment. Self-efficacy has a positive and significant effect on organizational commitment. Organizational commitment is not able to mediate between job satisfaction and employee performance. Organizational commitment can mediate between work self-efficacy and employee performance.